Komi can't communicate. Volume 4 - Oda, Tomohito, 1991-; Werry, John (Translator) (Shōnen Sandē komikkusu., 2019)
"Socially anxious high school student Shoko Komi's greatest dream is to make some friends, but everyone at school mistakes her crippling social anxiety for cool reserve! Luckily she meets Tadano, a timid wallflower who decides to step out of his comfort zone in order to help her achieve her goal of making 100 friends... School is out for the summer, and Komi is still getting used to this strange new world of having friends. She's discovering that friendship doesn't automatically save you from awkward situations with people, but the more time she spends with her friends, the easier it all seems. And to her astonishment, for the first time in her life Komi isn't anxious for summer to end."--Provided by publisher.